2008
DOI: 10.1001/jama.299.23.2770
|View full text |Cite
|
Sign up to set email alerts
|

Ketosis-Prone Type 2 Diabetes Mellitus and <emph type="ital">Human Herpesvirus 8</emph> Infection in Sub-Saharan Africans

Abstract: INCE 1987, AN ATYPICAL PRESENtation of diabetes has emerged as one of the most frequent forms of diabetes in populations of African origin. [1][2][3][4][5] It is a diabetic syndrome characterized by an acute onset with severe hyperglycemia and ketosis or ketoacidosis requiring insulin therapy, followed by longterm insulin-free near-normoglycemic remission periods, 6,7 frequently interrupted by ketotic relapses. 3 Thus, it resembles type 1 diabetes mellitus (DM-1) at onset and prediabetes or type 2 diabetes mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
75
2
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(89 citation statements)
references
References 41 publications
8
75
2
4
Order By: Relevance
“…A significant association of HSV-1, 2 seropositivity with ketonuria hyperglycaemia was found in this study. This agrees with the reports of other workers: Eugene et al [3] reported an association of herpes virus with DM-2 in patients of Sub-Saharan African origin where they recorded 87.7% seropositivity to HHV-8 in ketosis-prone DM-2. Yuhua et al [6] also reported an association of herpes simplex with diabetes..…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A significant association of HSV-1, 2 seropositivity with ketonuria hyperglycaemia was found in this study. This agrees with the reports of other workers: Eugene et al [3] reported an association of herpes virus with DM-2 in patients of Sub-Saharan African origin where they recorded 87.7% seropositivity to HHV-8 in ketosis-prone DM-2. Yuhua et al [6] also reported an association of herpes simplex with diabetes..…”
Section: Discussionsupporting
confidence: 92%
“…In this category, a degree of hyperglycaemia sufficient to cause pathologic and functional changes in various target tissue, but without clinical symptoms, may be present for a long period of time before diabetes is detected [1,2]. Several millions of people have diabetes globally including Africa [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, an 'atypical type 2' syndrome has been described in Africa, where initial insulin-dependence may later remit [4]. A viral aetiology for this type of diabetes has been suggested [5].…”
Section: Introductionmentioning
confidence: 99%
“…Among possible candidates, we focused on human herpesvirus-8 (HHV-8). We found a high association between KPD and HHV-8 infection and evidenced that this virus was able to infect human ␤-cells in vitro (25).…”
Section: Nefa Suppressionmentioning
confidence: 65%